2020
DOI: 10.1002/lno.11561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cell size on cellular Zn and Cd and Zn‐Cd‐CO2 colimitation of growth rate in marine diatoms

Abstract: Cadmium (Cd) can serve as nutrient in marine diatoms by partially replacing zinc (Zn) in Zn‐limited cells. A major basis for this is the replacement of Cd for Zn in a Cd‐containing carbonic anhydrase (CDCA) needed for cellular acquisition of CO2. As a result of these interactions, cells can become colimited by Zn, Cd, and CO2. Large cell size should restrict the cellular uptake of Zn, Cd, and CO2 due to decreasing surface to volume ratios and limitation of diffusive flux of these nutrients to the cell surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A recent field study by Morel, et al [ 48 ] in the eastern tropical South Pacific revealed that the substitution of Cd and Co for Zn occurred when dissolved Zn levels were extremely low and not necessarily with the lowest pCO 2 conditions. This further suggests that diatoms in the marine environment may be co-limited by Zn-Cd-Co and CO 2 [ 49 ]. To date, the cellular quotas of Zn attached to CA in marine phytoplankton remain an open question.…”
Section: Biological Function Of Eca In the Marine Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent field study by Morel, et al [ 48 ] in the eastern tropical South Pacific revealed that the substitution of Cd and Co for Zn occurred when dissolved Zn levels were extremely low and not necessarily with the lowest pCO 2 conditions. This further suggests that diatoms in the marine environment may be co-limited by Zn-Cd-Co and CO 2 [ 49 ]. To date, the cellular quotas of Zn attached to CA in marine phytoplankton remain an open question.…”
Section: Biological Function Of Eca In the Marine Environmentmentioning
confidence: 99%
“…Some species are likely to utilize Cd, Co or even newly found Mn as a cofactor, and such estimations are likely to be very uncertain within natural assemblages. Trace metal quotas in marine phytoplankton also depend on cell size [ 49 , 51 ]. A holistic approach is needed to resolve the coupling of marine trace metal chemistry to total CA expression and activity in natural phytoplankton assemblages.…”
Section: Biological Function Of Eca In the Marine Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 4-9 L of surface waters was filtered onto acid-cleaned 0.22 µm polycarbonate membrane filters. For PFe intra samples, in order to remove metal bound to the cell surface, cells were exposed twice to an oxalate-EDTA solution for 5 min and rinsed nine times with Chelex-cleaned 0.56 mol L −1 NaCl solution (Li et al, 2020). PFe total and PFe intra concentrations were then determined by inductively coupled plasma mass spectrometry (ICP-MS 7700x, Agilent).…”
Section: Particulate Fe Concentrationmentioning
confidence: 99%
“…Briefly, 4-9 L of surface waters were filtered onto acid-cleaned 0.22-μm polycarbonate membrane filters. For PFeintra samples, in order to remove metal-bound to the cell surface, cells were exposed twice to an oxalate-EDTA solution for 5 minutes and rinsed nine times with Chelex-cleaned 0.56 mol L -1 NaCl solution (Li et al, 2020).…”
Section: Particulate Fe Concentrationmentioning
confidence: 99%